KOMPARASI MEDIA PEMBELAJARAN PADA DUA KURIKULUM YANG BERBEDA YANG DIGUNAKAN PADA PEMBELAJARAN BIOLOGI DI SMAN SEKABUPATEN KLATEN - Rio Christy Handziko; Cantik Anggita Fifa Brazilyatna (Bioedukasi Jurnal Pendidikan Biologi, 2026)
This study aims to (1) analyse the media used by teachers during the pursuit of high school biology lessons in Klaten Regency in the implementation of the 2013 Revised Curriculum and the Merdeka Curriculum; (2) analyse the background of the use of these media during the learning process in the implementation of the 2013 Revised Curriculum and the Merdeka Curriculum; (3) and analyse the differences in the media used between the implementation of the 2013 Revised Curriculum and the Merdeka Curriculum. This research is a descriptive method with a qualitative approach. The data collection technique was carried out by observation, interview, and documentation and the analysis technique used data reduction, data presentation, and conclusion drawing. The results of this study show: (1) the types of media used by biology teachers in the implementation of the two curriculum consist of four types of media, namely visual, realia, audio-visual, and interactive multimedia; (2) the reasons for biology teachers in Klaten Regency to use the main media are their practicality and ease of making and implementing them, both in the implementation of the 2013 Revised Curriculum and the Merdeka Curriculum; (3) there is no significant difference in the use of media by high school biology teachers in Klaten Regency between the implementation of the 2013 Revised Curriculum and the Merdeka Curriculum.Kata kunci: media pembelajaran, guru biologi, kurikulum 2013 revisi, kurikulum merdeka